The author and the reader – “Us and them” in Maria Edgeworth’s texts for children and young adults - Mazurek, Monika (Adam Mickiewicz University, 2007)
The paper attempts to tackle the hyphenated self of Maria Edgeworth as Anglo-Irish writer in her books for children and young adults, reflected not only in the fact of the occasional introduction of Irish characters or Irish setting but also at the deeper level of the identity of the narrative voice and the implied reader of these texts. It attempts to show that the Anglo/Irish ratio in the narrative voice of Edgeworth’s texts is a fluctuating value, defining itself in the opposition to the implied reader, whose identity is in turn constantly changing sides as well, hovering between the poles of “us” and “them”.